Analisis Karakteristik Dewan Direksi dan Struktur Kepemilikan terhadap Manajemen Laba Perusahaan di BEI 2016-2020 - Mardianto Mardianto; Chintia Chintia (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to investigate the influence of women's boards of directors on earnings management. The dependent variable in this study is earnings management using the Discretionary Accruals measurement method with the Modified Jones Model. The independent variables used are women board of directors, board size, board independence, audit quality, family ownership, blockholder ownership, leverage, Return on Assets (ROA), and firm size. This study used a data sample of 381 companies with the period of 2016 to 2019 with a purposive sampling method. The research data tested by panel regression testing using Eviews and SPSS application. The results of this study are women board of directors, board size, board independence, audit quality, family ownership, blockholder ownership, and firm size do not have a significant effect on earnings management. Meanwhile, leverage has a significant negative effect on earnings management and Return on Assets (ROA) has a significant positive effect on earnings management.